Turning Tables in the Time of Pandemic: Radical Reversals and Progressive Alliances in America’s Restaurant Industry - Simon, Lucy Nash (Tufts Archival Research Center, 2021)
This thesis examines how the effects of COVID-19 exacerbated the pre-existing issues in the America’s restaurant industry and how the industry has responded. Since the second half of the 20th century, the American restaurant has been a paradigmatic entity grappling with issues central to critical thinking about food systems: environmentalism, identity, politics, labor, economics, and culture. The onset of the COVID-19 pandemic posed unprecedented challenges, but also insight into the industry. While the peril caused by the pandemic is by no means good, COVID has created conditions which drew back the veil of hospitality that represses difficulty and instability, which, coupled with an increase in media attention and care for the restaurants, provides a unique opportunity to examine the industry’s structural issues and how this moment may be fueling resilience through reinvention., In the thesis, I trace the history of US restaurants from the restaurant’s genesis in 18th century France to America’s contemporary postindustrial economy; analyze restaurant “pivots” in response to specific effects of the pandemic; and use tipping as a case study to understand how bound restaurants are to issues of race, class, gender, and status, and what potential might exist in the present moment to address underlying problems stemming from these issues. In applying a broad theoretical framework intended to address the larger food system, I show how restaurants represent a convergence of systemic issues with the pressures and expectations of commodified hospitality to create unique conditions of unsustainable performance and public image. Finally, by revealing how the pandemic induced surprising alliances across the restaurant industry and with greater society at large, I suggest that new forms of association are already supporting progressive changes to the restaurant’s structural inequalities to help carve out a more sustainable and equitable future.; Advisor: Cathy Stanton